IMPACT OF E-MARKETING IN SUPPORTING MSMES AFTER COVID-19 PANDEMIC - Oktavianty Oktavianty; Wahid Wahid; Ahmad Farhan; Alamsyah Alamsyah (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
Covid-19 Pandemic has create change in economic structure, causing lots of business to shut down during its time. Micro, small, and medium enterprises (MSMEs) are highly affected by the pandemic. Policy such as lockdown have prevent physical activity of trade. In order to survive in this condition many of SMEs owner have to generate innovation and creativity. One of the main key driver for surviving covid-19 pandemic are the use of E-Marketing strategy. In implementing EM ones have to understand the basic knowledge of technology and have the capability to learn new thing. The purpose of this paper is to understand E-Marketing, and how SMEs have adapt to it during the pandemic and how SMEs owner behavior after pandemic in term of continuing using EM. The result of this paper indicate the adaptability of SMEs owner to use EM during pandemic, EM also have contribute a lot to SMEs productivity during pandemic, lastly its stated that SMEs owner will continue to use EM to improve the development of their shop, store, or company